Prevalence of Smoking among Medical Students in Kathmandu, Nepal - Pradhananga, Srijana; Singh, S.; Panta, P.P. (Nepal Medical College Journal, 2019)
Smoking is a leading risk factor for early death and disability worldwide. Medical students and physicians are the ideal persons to educate patients about hazards of smoking. Today’s medical students will play a prominent role in future to prevent and control tobacco use. Still, the problem of smoking among the medical students is common worldwide but the pattern and extent of the problem varies from place to place. Aim of this study was to find out prevalence of smoking among medical students, factors contributing to their smoking habits, their exposure to passive smoking and to know about their knowledge about smoking related health problems. This is a cross sectional study, conducted among all first and second year MBBS students during July-September 2018. Self administered questionnaire were given to all the participants and collected after it was filled up. One hundred seventy four students participated in the study. Prevalence of smoking was 5.2% and all the students who smoked were male. The most important cause for initiation of smoking was peer pressure (56%). The average cigarettes smoked was seven sticks per day. Though 80% students knew about hazards of passive smoking, almost half of them were exposed to passive smoking. In our study we found that most of the students do not counsel their patients regarding hazards of smoking and only few participants were found to advise and encourage their patients to quit smoking.